Agronomic evaluation of sub1-introgressed black rice lines under rainfed lowland conditions in South Sumatra - Fikri Adriansyah; Entis Sutisna Halimi; Septiani Septiani (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2026)
Rice (Oryza sativa L.) is a major staple crop, and black rice is increasingly valued for its nutritional and economic importance. In South Sumatra, Indonesia, rainfed lowland swamp ecosystems offer substantial potential for rice cultivation, but productivity is constrained by alternating flooding and drought stress. The introgression of the Sub1 gene provides tolerance to submergence and supports the development of adaptive black rice cultivars. This study aimed to evaluate the agronomic performance of six black rice lines carrying the Sub1 gene under rainfed lowland conditions. The experiment was conducted using a randomized complete block design with three replications. Agronomic traits, including phenology, tillering, yield components, and grain yield, were recorded and analyzed using analysis of variance, correlation, and principal component analysis (PCA). Significant differences among genotypes were observed for most agronomic traits, indicating substantial genetic variability. Regita5 and Febry1 showed superior performance, producing the highest grain yields of 3.53 and 3.37 t/ha, respectively, supported by higher numbers of productive tillers and filled grains per panicle. Correlation and PCA results revealed that grain yield was primarily influenced by tillering capacity and grain production traits, whereas 100-grain weight and phenological traits contributed weakly or negatively. These findings demonstrate that black rice lines carrying the Sub1 gene, particularly Regita5 and Febry1, possess strong agronomic potential for cultivation and as breeding materials in stress-prone swamp ecosystems, contributing to sustainable rice production under climate variability.